'Well London' and the benefits of participation: results of a qualitative study nested in a cluster randomised trial. Issue 4 (2nd April 2014) - Derges, Jane; Clow, Angela; Lynch, Rebecca; Jain, Sumeet; Phillips, Gemma; Petticrew, Mark; Renton, Adrian; Draper, Alizon
Abstract : Background: Well London is a multicomponent community engagement and coproduction programme designed to improve the health of Londoners living in socioeconomically deprived neighbourhoods. To evaluate outcomes of the Well London interventions, a cluster randomised trial (CRT) was conducted that included a longitudinal qualitative component, which is reported here. The aim is to explore in depth the nature of the benefits to residents and the processes by which these were achieved. Methods: The 1-year longitudinal qualitative study was nested within the CRT. Purposive sampling was used to select three intervention neighbourhoods in London and 61 individuals within these neighbourhoods. The interventions comprised activities focused on: healthy eating, physical exercise and mental health and well-being. Interviews were conducted at the inception and following completion of the Well London interventions to establish both if and how they had participated. Transcripts of the interviews were coded and analysed using Nvivo. Results: Positive benefits relating to the formal outcomes of the CRT were reported, but only among those who participated in project activities. The extent of benefits experienced was influenced by factors relating to the physical and social characteristics of each neighbourhood. The highest levels of change occurred in the presence of: (1) social cohesion, not only pre-existing but also as facilitated by Well London activities; (2) personal and collective agency; (3) involvement and support of external organisations. Where the physical and social environment remained unchanged, there was less participation and fewer benefits. Conclusions: These findings show interaction between participation, well-being and agency, social interactions and cohesion and that this modulated any benefits described. Pathways to change were thus complex and variable, but personal well-being and local social cohesion emerged as important mediators of change.